How We See Area and Why It Matters. Issue 7 (July 2021) - Yousif, Sami R.; Keil, Frank C.
Abstract : A large and growing literature examines how we see the visual quantities of number, area, and density. The literature rests on an untested assumption: that our perception of area is veridical. Here, we discuss a systematic distortion of perceived area and its implications for quantity perception more broadly.